LANGUAGE AS A TOOL FOR PROPAGANDA AND MISINFORMATION IN CONFLICT ZONES: IMPLICATIONS ON ANAMBRA RESIDENTS AND INSECURITY - Amaka Yvonne Okafor (Adisam Publisher, 2025)
Language holds immense power in shaping perceptions, constructing realities, and influencing social behavior, especially in contexts of conflict. This study employed a qualitative systematic review to examine how language is used as a tool for propaganda and misinformation in conflict zones, focusing on Anambra State. Literature from 2010 to 2024 was sourced from credible databases such as Google Scholar, JSTOR, AJOL, and Scopus, using keywords related to language, conflict, and insecurity in Southeast Nigeria. Only empirically grounded studies were included. Data were analyzed thematically, revealing recurring strategies like emotive language, ethnic appeals, and framing government as adversaries. The review followed PRISMA guidelines to ensure transparency, credibility, and minimize bias in presenting how language influences public perception and insecurity. The findings reveal that emotionally charged and biased language, often shared through digital platforms and informal channels, plays a significant role in deepening distrust, spreading fear, and eroding public confidence. In Anambra, where underlying tensions exist, such linguistic manipulation worsens insecurity and fragments social cohesion. The study also emphasizes the role of media literacy in helping individuals critically evaluate information, resist manipulative narratives, and foster informed public discourse. Additionally, the research highlights how language can serve as a bridge for peacebuilding when used inclusively and responsibly. Language, therefore, is central to both the challenges and solutions related to insecurity in conflict-affected societies.